2016
DOI: 10.1007/s11695-016-2444-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Laparoscopic Sleeve Gastrectomy for Morbid Obesity: a Systematic Review and Meta-analysis

Abstract: We aim to review the available literature on obese patients treated with robotic or laparoscopic sleeve gastrectomy, in order to compare the clinical outcomes and intraoperative parameters of the two methods. A systematic literature search was performed in PubMed, Cochrane Library and EBSCOhost databases, in accordance with the PRISMA guidelines. Sixteen studies met the inclusion criteria incorporating 29,787 patients. Robotic sleeve gastrectomy (RSG) technique showed significantly higher mean operative time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 26 publications
2
16
0
6
Order By: Relevance
“…The reason behind this factor is that Saudi students mainly consume junk 15 as compared to our study. In Kuwaiti university students the said ratios were thirty two % and 8.9%, whereas in United Arab Emirates the percentage for male overweight students was 35% and almost similar ratio was observed in USA [16][17][18] . Prevalence of underweight in this study is higher than many of other reported studies.…”
Section: Discussionmentioning
confidence: 62%
“…The reason behind this factor is that Saudi students mainly consume junk 15 as compared to our study. In Kuwaiti university students the said ratios were thirty two % and 8.9%, whereas in United Arab Emirates the percentage for male overweight students was 35% and almost similar ratio was observed in USA [16][17][18] . Prevalence of underweight in this study is higher than many of other reported studies.…”
Section: Discussionmentioning
confidence: 62%
“…That decrease might be explained by globally increased application of sleeve gastrectomy for weight loss purposes, which can be more easily performed by laparoscopic technique . Robotic bariatric surgery has been shown to be as safe as laparoscopic counterpart . The two previous meta‐analyses revealed that increased operative time and higher costs are the main limitations robotics in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic bariatric surgery has been shown to be as safe as laparoscopic counterpart . The two previous meta‐analyses revealed that increased operative time and higher costs are the main limitations robotics in this field. However, robotic surgery provides two important advantages that overcome the limitations of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations